Safety and Efficacy of Programmed Cell Death 1 and Programmed Death Ligand-1 Inhibitors in the Treatment of Cancer: An Overview of Systematic Reviews - Ou, Shun-Long; Luo, Jing; Wei, Hua; Qin, Xiao-Li; Du, Su-Ya; Wang, Song; Jiang, Qian (Frontiers in Immunology, 2022)
Background An influx of system reviews (SRs) of PD-(L)1 inhibitors in the treatment of cancer with different methodological quality and inconsistent results have been published, which brings confusion to clinical decision making. The aim of this study was to comprehensively evaluate and summarize the current evidence of PD-(L)1 inhibitors in the treatment of cancer. Methods A comprehensive search was conducted for SRs of PD-(L)1 inhibitors on cancer in eight databases with a cut-off date of January 1, 2022. Two authors independently identified SRs, extracted data, assessed the report quality according to the guidance of the PRISMA statement, evaluated the methodological quality by the AMSTAR 2, and appraised the quality of evidence by the GRADE. Results A total of 172 SRs met the inclusion criteria. The report quality of SRs included was quite good with 128 (74.42%) SRs were high quality and else were moderate quality. The methodological quality was alarming with only 1 (0.58%) SR was high quality, 5 (2.91%) SRs were low quality, the other 166 (96.51%) SRs were critically low quality. For GRADE, 38 (3.77%) outcomes had high quality evidence, 288 (28.57%) with moderate, 545 (54.07%) with low and 137 (13.59%) with critically low quality evidence. Current evidence indicated significantly advantages efficacy in non-small cell lung cancer, small cell lung cancer, hepatocellular carcinoma, malignant melanoma, renal cell carcinoma, and urothelial carcinoma, breast cancer, head and neck squamous cell carcinoma with PD-L1 expression level ≥ 1% treated with PD-(L)1 inhibitors, while the evidence in gastroesophageal and colorectal tumors were still controversial. PD-(L)1 inhibitors monotherapy associated with lower frequency of any grade and high grade adverse events (AEs). The incidence of any grade and high grade AEs of PD-(L)1 inhibitors in combination with other therapies was no lower than the controls. But PD-(L)1 inhibitors associated with higher frequency of any grade and high grade immune-related adverse events. Conclusions PD-(L)1 inhibitors appear to be effective and safe for cancer, with the exception of gastrointestinal tumors, but the quality of the evidence is not convincing. Future studies should improve methodological quality and focus on trial sequential analysis of subgroups and safety.